Blend of organic acids improves gut morphology and affects inflammation response in piglets after weaning - de Groot, Nienke; Fariñas, Fernando; Cabrera-Gómez, Carolina G.; Pallares, Francisco J.; Ramis, Guillermo (Frontiers in Animal Science, 2024)
Weaning is a stressful period in a piglet's life, when many morphological and functional changes occur in the gastro-intestinal tract. Examples are an alteration of the barrier function and an increase in production of cytokines, suggesting the immune system of the GIT is activated after weaning. The goal of this study was to evaluate the effect of a commercially available feed additive based on short and medium chain fatty acids on supporting intestinal health and reduce inflammation in the intestine of post-weaning piglets. Seventy piglets were divided over 2 treatments, a control diet and a blend of short and medium chain fatty acids, including butyrate. and oOn day 0, day 15, day 30 and day 45 after weaning blood samples and intestinal tissue samples were collected from sacrificed piglets. Blood and tissue samples were analysed for cytokine gene expression, and tissue samples from jejunum and ileum were analysed on morphology and gene expression of tight junctions. Results show that the use of a blend of short and medium chain fatty acids, including butyrates, improved intestinal morphology, measured by villous length and v/c ratio, reduced expression of tight junction proteins and influenced cytokine production in the intestine, implicating that the use of organic acids as feed additives potentially can reduce damage caused by weaning to the intestinal barrier and due to the higher absorption capacity of the villi potentially improve nutrient absorption. Weaning is a stressful period which in nature occurs between 10 to 12 weeks of age in a gradually matter, around the time when the GIT matures. In professional pig farming weaning occurs between three to four weeks of age (Worobec, Duncan and Widowski, 1999), and it can cause many morphological and functional changes in the GIT (